Effect of Oxidizing Medium on Synthesis Gas Content at Solid Fuel Gasification; MATEC Web of Conferences; Vol. 72 : Heat and Mass Transfer in the System of Thermal Modes of Energy – Technical and Technological Equipment (HMTTSC-2016) - Korotkikh A. G. Aleksandr Gennadievich (2016, 2016)
Title screen